Correlation between Cholinesterase Levels and Blood Glucose Levels in Farmers Exposed to Organophosphate Pesticide in Desa Sukorambi Kabupaten Jember - Sofiannisa Achmadila; Kristianningrum Dian Sofiana; Yudha Nurdian (Faculty of Medicine, University of Jember, 2019)
The use of organophosphate pesticides by farmers can cause long-term health risks, one of which is an increase in blood glucose levels. This study aims to determine whether there is a relationship between the levels of cholinesterase as an indicator of exposure to organophosphate pesticides and blood glucose of farmers in Sukorambi Village, Jember Regency. Secondary data in the form of general characteristics of the sample were obtained through interviews, while the primary data was obtained from examining the levels of cholinesterase and blood glucose levels of farmers at the Biochemical Laboratory of the Faculty of Medicine, Jember University. The research method is observational-analytic with cross-sectional study design. Based on the results of statistical analysis using the Spearman correlation test (p = 0.05), it was concluded that there was no significant relationship between the two variables (p = 0.0802).